P115 Epidemiology, Characteristics and Management of Non Tuberculous Mycobacteria in a Devon Population. (14th November 2013) - Mitchelmore, P; Sharp, C; Unsworth, R; Anning, L; Burden, T; Withers, N
Abstract : Introduction and Objectives: Non-Tuberculous Mycobacteria (NTM) are ubiquitous species typically residing in soil and water. Their presentation as pathogens in disease is believed to be rising with the most common site of isolation being pulmonary. We have examined the epidemiology and characteristics of NTM presenting to our clinic over the period 2005–2012. Method: Our database, including all patients with at least one identification of an NTM during the period of 2005–2012, was reviewed. Data presented includes all incidences documented from 2009 onwards, with additional data from before 2009 used to gain further demographic information about the population. Those who were non-resident in the area were excluded. The data was collected from Clinical Letters, Radiology and Pathology records, with data being reviewed by the lead investigator and one other in cases where information was uncertain. Results: Data was obtained from 74 new isolations, with a total of 11 different species of NTM identified. Patients presenting had a median age of 68 and a range of 8–88 years. 39(53%) were female and 46 (62%) were "one-off" isolates. M. Avium-intracellulare (MAI) was the most frequently reported isolate (42 cases, 57%) followed by M. Chelonae (8, 11%) and M. Xenopi (6, 8%). The majority (68, 92%) of isolates were pulmonary with 45(66%) of these found in standard sputum culture. Most frequently recorded co-morbidities were bronchiectasis (35 cases, 47%) and COPD (20, 27%). Of the total of 74 cases only 24 (32%) had received treatment by the time of our survey. The overall rates for eradication and subsequent relapse in those treated patients were 50% and 25% respectively for the total population and 57% and 38% for those with MAI. At completion of the study the mortality rate within 2 years of the first positive sample was 18%. Conclusion: In keeping with previous UK surveys, the majority of isolates in our population were pulmonary with MAI being the most frequently seen species of NTM. In those in whom treatment was indicated low eradication rates and significant relapse rates confirm complexity of managing this population of patients.